Establecer condiciones de operación del nuevo proceso de elaboración de cerveza artesanal tipo APA en la micro cervecería Dope D.C. (2019)
Dope D.C is a microenterprise responsible for the production of craft beer, located in the city of Bogotá; Thanks to the great variety and quality of products, it is necessary to increase their production capacity, for this reason they decide to invest in a cooking room with a production capacity of 120L. Because of this, the student must establish the operating conditions in each of the stages and produce an APA style.